2014
DOI: 10.1002/er.3253
|View full text |Cite
|
Sign up to set email alerts
|

Pt/zirconia catalyst for hydrogen generation from HI decomposition reaction of S-I cycle

Abstract: Summary Hydrogen energy is considered as one of the ideal solutions for the fulfilment of the ever increasing energy demand. It is mainly due to the following two reasons: firstly, it can be produced from a very abundant source, that is, water; and secondly, it does not leave any harmful effect on the environment. Thermochemical cycles are amongst the most promising ways to generate hydrogen from water in an environment‐friendly manner. Sulfur–iodine cycle is one of the most efficient thermochemical cycles. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Reactive distillation has an advantage of combining reaction and separation in a single step leading to overall shift of equilibrium towards production of I 2 and H 2 . Pt based catalysts supported on different supports like carbons [27][28][29][30] and oxides [31][32][33][34] have been used as catalysts for HI decomposition reaction during this process. There are few reports on use of nickel based catalyst systems also [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive distillation has an advantage of combining reaction and separation in a single step leading to overall shift of equilibrium towards production of I 2 and H 2 . Pt based catalysts supported on different supports like carbons [27][28][29][30] and oxides [31][32][33][34] have been used as catalysts for HI decomposition reaction during this process. There are few reports on use of nickel based catalyst systems also [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, we had studied platinum compared supported platinum catalysts with varying nature of porosity of carbon supports, i.e. microporous and mesoporous [27] and mesoporous zirconia support [34]. In the current study we plan to extend the studies to catalyst based on platinum supported on planar carbon support.…”
Section: Introductionmentioning
confidence: 99%
“…Precious metal based catalysts (supported Pt, Pd, and Ir catalysts) have also been studied extensively for this reaction [11,17,18]. Few reports have shown that the activity of Pt supported catalyst was influenced by the support [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ZrO 2 has been used as a catalyst and support in different catalytic reactions such as solid-oxide fuel cells, ethanol reforming, hydrogen generation and hydrogenation [13–17]. It is reported to be more inert in acidic reaction environments [18] and a better catalyst/support than other materials such as SiO 2 , TiO 2 , and Al 2 O 3 [19]. Recently, we reported the usage of ZrO 2 and Pt-doped ZrO 2 nanoparticles for CO oxidation [20].…”
Section: Introductionmentioning
confidence: 99%